1988
DOI: 10.1093/infdis/158.2.372
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Protection by B Subunit-Whole Cell Cholera Vaccine Against Diarrhea Associated with Heat-Labile Toxin-Producing Enterotoxigenic Escherichia coli: Results of a Large-Scale Field Trial

Abstract: The B subunit (BS) of cholera toxin and that of the heat-labile enterotoxin (LT) of enterotoxigenic Escherichia coli (ETEC) are antigenically similar. We therefore assessed whether a combined cholera toxin BS/whole-cell (BS-WC) oral vaccine against cholera conferred cross-protection against LT-producing ETEC (LT-ETEC) diarrhea in a randomized, double-blind field trial among rural Bangladeshi children and women. The 24,770 persons who ingested two or more doses of BS-WC vaccine were compared with 24,842 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
127
2
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(136 citation statements)
references
References 18 publications
1
127
2
3
Order By: Relevance
“…However, there is an oral cholera vaccine composed of killed wholecell Vibrio cholera, plus the B subunit of cholera toxin, which provides some cross-protection against LT-and LT/ ST-producing strains of ETEC. 13,14 The basis for the crossprotective efficacy of the cholera vaccine lies in the fact that the LT of ETEC is antigenically similar to cholera toxin in that it can elicit sufficient cross-reacting antibodies to LT. 13 Although anti-LT immunity is important in disease prevention, many ETEC isolates produce ST without LT. 4 ST is poorly antigenic and unrelated to LT, so other common antigens must be evaluated as potential vaccine components.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is an oral cholera vaccine composed of killed wholecell Vibrio cholera, plus the B subunit of cholera toxin, which provides some cross-protection against LT-and LT/ ST-producing strains of ETEC. 13,14 The basis for the crossprotective efficacy of the cholera vaccine lies in the fact that the LT of ETEC is antigenically similar to cholera toxin in that it can elicit sufficient cross-reacting antibodies to LT. 13 Although anti-LT immunity is important in disease prevention, many ETEC isolates produce ST without LT. 4 ST is poorly antigenic and unrelated to LT, so other common antigens must be evaluated as potential vaccine components.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies have shown that anti-LT immunity protects against ETEC-induced diarrhea in human (15)(16)(17). LT is structurally and biologically similar to CT (2,18), and several studies have demonstrated cross-protective immunity between CT and LT (19)(20)(21). It was therefore an obvious and important question to address whether CT-specific mucosal IgA induced by oral MucoRice-CTB vaccine could provide cross-protective immunity against LT-induced diarrhea and, if so, whether it could also provide protection against diarrhea induced by LT-producing ETEC (LT-ETEC).…”
mentioning
confidence: 99%
“…A vaccine that offers some protection against diarrhea caused by infections with strains producing LT is already available (3). In contrast to LT, STp and STh are small molecules that normally do not induce an immune response (12).…”
mentioning
confidence: 99%